The Effect of Company Size, Company Profitability, Previous Audit Opinion, and Kap Size as A Determiner of Going Concern Audit Opinions (Empirical Study on Non-Financial Services Companies Listed on The Indonesia Stock Exchange) - Belinda Stella Asherina Djunaedi; Fransisca Depitaria Meylanti Manurung; Julyane Tomy; Tiara Regina; Sylvia Fetty Elvira Maratno (Journal of Social Science, 2022)
The study aims to determine the effect of firm size on the acceptance of going concern audit opinion, the effect of corporate profitability on the acceptance of going concern audit opinion, the effect of previous year's audit opinion on the acceptance of going concern audit opinion, the effect of accounting firm size on the acceptance of going concern audit opinion, and the simultaneous influence of company size, company profitability, previous year audit opinion, and accounting firm size on the acceptance of going concern audit opinion. The research method used in this research is a hypothetico-deductive method which is a systematic approach and valuable to produce knowledge to solve fundamental and managerial problems. Initially, the researcher determined the theme or problem area. Furthermore, the researcher identified a problem formula. Based on theories and previous research, the researcher made the hypothesis to be tested. This study focused on non-financial service companies listed on the Indonesia Stock Exchange. The results of the partial test show that there is no significant influence of firm size ongoing concern opinion, there is the significant influence of profitability ongoing concern opinion, there is the significant influence of previous audit opinion of with going concern opinion, and there is no significant influence of accounting firm size ongoing concern opinion. The simultaneous testing result indicates that the firm size, the company profitability, the previous year's audit opinion, and the size of the accounting firm influence the acceptance of going concern audit opinion.